Federated learning for IoMT applications: a standardization and benchmarking framework of intrusion detection systems - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
Federated learning for IoMT applications: a standardization and benchmarking framework of intrusion detection systems by Alamoodi, Abdullah Hussein